2017
DOI: 10.1038/s41598-017-05520-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gratitude meditation on neural network functional connectivity and brain-heart coupling

Abstract: A sense of gratitude is a powerful and positive experience that can promote a happier life, whereas resentment is associated with life dissatisfaction. To explore the effects of gratitude and resentment on mental well-being, we acquired functional magnetic resonance imaging and heart rate (HR) data before, during, and after the gratitude and resentment interventions. Functional connectivity (FC) analysis was conducted to identify the modulatory effects of gratitude on the default mode, emotion, and reward-moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Expressing gratitude is known to promote positive mind-sets and to reduce stress levels (Emmons & McCullough, 2003). During gratitude (vs. resentment) experience, decreased heart rate as well as temporal synchronization of heart rate and amygdala-based functional connectivity with the audiovisual sensory regions has been found in an fMRI study involving healthy subjects (Kyeong, Kim, Kim, Kim, & Kim, 2017). Thus, besides its effectiveness in reducing unpleasant short-term affective states, the use of gratitude could be to limit uncomfortable physical sensations.…”
Section: Ta B L E 3 Changes In Psychological Measures Between Pre Joumentioning
confidence: 99%
“…Expressing gratitude is known to promote positive mind-sets and to reduce stress levels (Emmons & McCullough, 2003). During gratitude (vs. resentment) experience, decreased heart rate as well as temporal synchronization of heart rate and amygdala-based functional connectivity with the audiovisual sensory regions has been found in an fMRI study involving healthy subjects (Kyeong, Kim, Kim, Kim, & Kim, 2017). Thus, besides its effectiveness in reducing unpleasant short-term affective states, the use of gratitude could be to limit uncomfortable physical sensations.…”
Section: Ta B L E 3 Changes In Psychological Measures Between Pre Joumentioning
confidence: 99%
“…Physical activity naturally increases heart rate, but also just thinking about physical activity may increase heart rate 4 . Similarly, mental exercises such as meditation can reduce heart rate 5 . The effect of cognition on heart rate is perhaps even more direct than these traditional accounts 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, MRI studies exploring the neural correlates of meditation have revealed important insights into how this mental training changes brain function and structure (Brewer et al, 2011; Kilpatrick et al, 2011; Froeliger et al, 2012; Hasenkamp et al, 2012; Taylor et al, 2013; Garrison et al, 2014; Marchand, 2014; Tang et al, 2015; Panda et al, 2016; Kyeong et al, 2017; Mooneyham et al, 2017; Marusak et al, 2018). Yet, little is known about how meditation influences the capability to transmit information across the whole-brain functional network.…”
Section: Introductionmentioning
confidence: 99%